Application of genetic algorithm to improve voltage regulation of self-excited induction generator in a wind energy conversion system. (4th December 2006) - Joshi, Dheeraj; Sandhu, K.S.; Soni, M.K.
Self-excited induction generators have been found to be most suitable for wind energy conversion in remote locations. In this paper, an attempt has been made to improve the voltage regulation of self-excited induction generator (SEIG) using series compensation. A new methodology has been developed to compute the generated frequency (a), magnetising reactance (Xm ), shunt capacitance (Csh ) and series capacitance (Cse ), using Genetic Algorithm (GA). Computed results using proposed modelling have been compared with experimental results. A close agreement between the computed and experimental results confirms the validity of the approach adopted.